Determinants of Healthy Lifestyle Behaviors among Young Adults in the Digital Era - Reni (Journal of Public Health Indonesian, 2026)
Rapid digitalization has reshaped how young adults acquire health information, engage with health-promoting technologies, and construct daily lifestyle routines, yet evidence on the determinants of healthy lifestyle behavior in this population remains fragmented across disciplinary silos. This narrative review synthesizes findings from twenty-five peer-reviewed studies published between 2021 and 2026 to develop an integrative framework explaining the determinants of healthy lifestyle behavior among young adults in the digital era. Using a structured search of Scopus, PubMed, Web of Science, JMIR, and Frontiers databases, studies were screened, thematically coded, and narratively synthesized across five determinant domains: digital health literacy, online health-information seeking and social media engagement, digital health interventions and mobile applications, psychological and dispositional factors, and sociodemographic-cultural context. Findings indicate that digital health literacy and purposeful social media engagement consistently predict better dietary, physical-activity, and health-monitoring behaviors, while psychological dispositions such as consideration of future consequences, self-control, and sense of coherence moderate how digital exposure translates into sustained action. Digital interventions show promise but remain constrained by low long-term engagement and limited cultural adaptability. The novelty of this review lies in integrating literacy-based, behavioral, psychological, and contextual determinants into a single multi-level model, offering researchers, educators, and public-health practitioners a coherent evidence base for designing culturally responsive digital health-promotion strategies targeted at young adults.